Creating a base for the implementation of industry 4.0 in Kazakhstan - Moldakarimov, A.R. (KSU publ., 2020)
This article discusses the main priorities in the development of high-tech and high-tech industries. The characteristic features of medium and large enterprises as a modern production system, as well as the introduction of digital technologies in production and the gradual transition to international standards of Industry 4.0 are analyzed. The necessity of adaptation of the state programs on branch directions for stimulation of introduction of digitalization and modernization of productions is revealed and proved. On the basis of the study, the author proposes to develop the necessary measures of state support, in terms of financial incentives for preferential lending and leasing programs, innovative grants, in order to expand and stimulate private sector initiatives in the field of digitalization, as well as to address infrastructure issues.
Keywords: High-performance; Innovation; innovation system; modern production system; digitalization; Industry 4.0.